Pengukuran Tahanan Isolasi Terminal Incoming Gardu Kubikel 20KV di PT Haleyora Power Region 3 Jawa Timur Area Mojokerto (Universitas Hasyim Asy`ari, 2023)
PT Haleyora Power is a subsidiary of PT PLN which is engaged in the operation and maintenance of electricity transmission and distribution networks. One of them is routine maintenance of the 20kv cubicle substation with the aim of maintaining the reliability of distribution in the electricity system. For Region 3 East Java, the Mojokerto area itself has 3 working areas, namely, Mojokerto, Jombang, and the Nganjuk area. In the process the cubicle is divided into 3 points, namely, incoming as input from the 20kv transformer output owned by PLN, metering is the part that functions to monitor (current, voltage, and electricity demand), the last is outgoing which is the 20kv output which will enter the transformer input customer/industry property. In this study, what was measured was insulation resistance using an insulation tester / megger and focused on the incoming terminal, the terminal points measured were between terminals r-s, r-t, s-t, r-n, s-n, and t-n. The minimum standard for measuring insulation resistance in a 20kv cubicle is 20MOhm. With an insulation resistance of more than 20MOhm, the insulation resistance obtained is good enough.